Endowing versatility and antibacterial ability to composite coating via a spraying strategy. Issue 12 (15th June 2023) - He, Simin; Liu, Wentong; Zheng, Hui; Guo, Ruibin; Liu, Nijuan; Mo, Zunli
Abstract: Study on polyphenylene sulfide coating with superhydrophobic and anti-corrosion has been made a significant enhancement, yet few of them have been applied to antibacterial research. This research innovatively compounded polyphenylene sulfide (PPS) with CuO/SiO2 nano filler, superhydrophobic and anti-corrosion CuO/SiO2 /PPS coating with antibacterial effect was obtained by air spraying. Through the test, the water contact angle of the composite coating reached 151.51 ± 1°, and the sliding angle decreased to 5 ± 1°. The electrochemical corrosion current density of the composite coating is 4 orders of magnitude lower than that of bare iron sheet, and the impedance reaches 780, 740 Ω cm 2 . After testing in acid, alkaline and salt solutions, the composite coating still shows promising chemical stability. Meanwhile, it shows positive performance in anti fouling and adhesion. Most importantly, the composite coating has a good inhibitory effect on the growth of Escherichia coli, Bacillus subtilis and Staphylococcus aureus, confirming the good synergistic effect of CuO and PPS. This work provides a new strategy for the multifunctional PPS composite coating. Graphical abstract: Image 1 Highlights: Composite coatings were prepared by a simple air spraying method. The addition of CuO in the coating filler makes the PPS coating antibacterial. The composite coating has excellent superhydrophobic, anti-corrosion, self-cleaning and anti-fouling properties. The corrosion current of the composite coating is 4 orders of magnitude lower than that of the initial substrate.